2021
DOI: 10.3390/axioms10030128
|View full text |Cite
|
Sign up to set email alerts
|

Logic-Sensitivity of Aristotelian Diagrams in Non-Normal Modal Logics

Abstract: Aristotelian diagrams, such as the square of opposition, are well-known in the context of normal modal logics (i.e., systems of modal logic which can be given a relational semantics in terms of Kripke models). This paper studies Aristotelian diagrams for non-normal systems of modal logic (based on neighborhood semantics, a topologically inspired generalization of relational semantics). In particular, we investigate the phenomenon of logic-sensitivity of Aristotelian diagrams. We distinguish between four differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, bitstring semantics is a combinatorial technique that allows us to systematically compute compact representations of the formulas that appear in a given diagram, thus providing a concrete grip on its logical behavior. The wideranging significance of the present paper should be clear, since logic-sensitivity and bitstring semantics are not only among the most important research topics in logical geometry today [8,13,15,38], but are also regularly discussed across the broad field of philosophical logic [2,16,23,27,28,31,32]. These two topics are well-understood by themselves, but the precise details of their interaction turn out to be far more complicated.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…On the other hand, bitstring semantics is a combinatorial technique that allows us to systematically compute compact representations of the formulas that appear in a given diagram, thus providing a concrete grip on its logical behavior. The wideranging significance of the present paper should be clear, since logic-sensitivity and bitstring semantics are not only among the most important research topics in logical geometry today [8,13,15,38], but are also regularly discussed across the broad field of philosophical logic [2,16,23,27,28,31,32]. These two topics are well-understood by themselves, but the precise details of their interaction turn out to be far more complicated.…”
Section: Introductionmentioning
confidence: 84%
“…Logic-sensitivity is a well-known phenomenon in logical geometry [8,13] and beyond [2,28,31,32]. In order to properly describe this phenomenon, we first need to introduce the notions of Aristotelian relations, diagrams and isomorphisms.…”
Section: Logic-sensitivity Of Aristotelian Diagramsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, historical scholarship has shown that Aristotelian diagrams for modal logic can be reconstructed from the works of many earlier authors, such as Theophrastus [6,7], Chrysippus [8,9], and Avicenna [10,11]. Today, Aristotelian diagrams not only appear in well-known textbooks on modal logic [12,13], but they are also used in applications of modal logic to a variety of philosophical and logical topics, such as paraconsistency [14,15], logic-sensitivity [16][17][18], and theories of truth [19,20]. It should be emphasized that all of these applications manifest a wide diversity of Aristotelian diagrams: next to the "ordinary" squares of oppositions, we also find several types of hexagons, octagons, and even more complex diagrams [21].…”
Section: Introductionmentioning
confidence: 99%